Texts that travel on the ship of illusions: the class diaries in a Sociology and Education course - Reyes Sandoval, Abril Atenea (2022)
This article explores the qualities of class diaries, a type of written text produced by first-year undergraduate students of Pedagogy at the National Autonomous University of Mexico (UNAM). The study is grounded on the concern for the effects of COVID-19 pandemic on school communities. Based on this problem, a content analysis is carried out with the aim of identifying what kind of expressions does the class diary make possible and what is its relevance in the context of emergency remote teaching. Firstly, it presents the theoretical framework of the class diary and the scenario where it is written. Subsequently, four primary categories emerge from the analysis of the texts: 1) the articulation of curriculum contents, 2) the aesthetic experience of their writing process, 3) undergraduate’s critical perspectives of their previous learning experiences, and 4) the scope for emotional engagement. It is concluded that the diaries are a valuable teaching technique to strengthen bonds of affection between teachers and students. It also promotes values such as cooperation, free expression, and dignifying work within the classroom, all of them urgent to reshape the school in times of global crisis.